Psychosomatic complaints in adolescence: Untangling the relationship between offline and online peer victimization, psychosomatic complaints and social support. Issue 4 (4th July 2017) - Sumter, Sindy R.; Baumgartner, Susanne E.
Abstract: Offline peer victimization has been linked to psychosomatic complaints. As peer victimization is no longer limited to adolescents' offline relationships, it is crucial that we investigate whether online peer victimization has similar negative consequences. To date, no study systematically investigated the unique contribution of online vs. offline peer victimization on psychosomatic complaints, and the possible protective effect of social support. The current study disentangled offline and online peer victimization by distinguishing four victim types: non-victims, offline, online, and dual victims ( N = 897, 9-to-18-year-olds). In addition, we assessed perceived social support from teachers, parents, friends and classmates. A main effect was found for victim type on psychosomatic complaints. Victims (offline or dual) reported more psychosomatic complaints than non-victims. Notably, online victims reported similar levels of psychosomatic complaints compared to non-victims. Furthermore, although social support from parents and classmates was related to fewer psychosomatic complaints, only limited support was found for a buffering effect of social support.